Nts on the Incidence and Damage of Flea Beetle (Phyllotreta Nigripes) and Thrips (Megalurothrips Usitatus) on Mungbean: NTS on the incidence and damage of flea beetle (Journal of the Asiatic Society of Bangladesh, Science, 2023)
An experiment was conducted to evaluate the effectiveness of different treatments for the management of flea beetles and thrips of mungbean using BARI Mung-6 as experimental material. Nine treatments, viz., T1 = Use of White sticky trap, T2= Bioneem plus (Azadirachtin) 1%EC @ 1 ml/L of water at 40 DAS, T3 = Virtako (Chlorantraniliprole + Thiamethoxam) 40 WG @ 0.15g/L of water at 40 DAS, T4 = Amithrin plus 3% WDG @ 1 ml/L of water at 40 DAS, T5 = Ecomec (Abamectin) 1.8 EC @ 1 ml/L of water at 40 DAS, T6 = Nitro (Chlorpyriphos + Cypermethrin) 505 EC @ 1 ml/l of water at 40 DAS, T7 = Raise (Chlorantraniliprole) 20 SL @ 3 ml/L of water at 40 DAS and T8 = control were applied. Data were recorded on the number of flea beetles per plant, leaf area damaged by flea beetles, number of thrips-infested flowers per plant, and number of thrips per 20 opened flowers. Results revealed that the lowest number of flea beetles (3.00/m2 plants) and the highest percent reduction (64.71%) of flea beetle population over control were recorded in Virtako 80 WG at 0.15 g/L of water-treated plots. The lowest percent damage (3.75%) of leaf area and the highest percent reduction (79.73%) of leaf area damage over control were observed in Virtako-treated plots. The lowest number of thrips population (1.50/20 flowers), the highest percent of thrips population reduction (85.37%) over control, the lowest number of infested flowers (0.88/20 flowers) by thrips, and the highest percent reduction (88.65%) of flower infestation over control were found in mungbean plants treated with Raise 20 SL @ 3 ml/L of water. A strong negative correlation between the number of flea beetles and total yield was observed. There were negative relationships between the number of thrips, percent flower infestation, and total yield. Therefore, the application of Virtako 80 WG at 0.15 g/L and Raise (Chlorantraniliprole) 20 SL at 3 ml/L were found to be the best treatments for controlling flea beetles and thrips on mungbean.J. Asiat. Soc. Bangladesh, Sci. 49(2): 225-235, December 2023